(untitled) (Journal of actual problems of jurisprudence, 2018)
‘Europe’s listed companies will be forced to reserve at least 40 per cent of their non-executive director board seats for women by 2020 or face fines and other sanctions under a proposal being drafted by the European Commission’. Although several EU countries – including France, Italy, Spain and the Netherlands – have already adopted their own national quotas, such hard limits have run into fierce resistance by Britain and Sweden, which currently have no limits. An official in the UK’s business department said the government had yet to see the commission’s proposal, but added: “Our position will still stand – we are opposed to legislation for quotas”. It is obviously controversial issue whether to treat the legislation for quotas as an inherent and indispensable instrument for board diversity and for the preservation of gender balance at all. In my personal opinion, it must be considered, insofar as the legislation for quotas already yields its fruits and renders benefits in some countries such as France, Italy, Spain, and Netherlands. However, UK and Sweden support exact and undeniable opposition to the adoption of quota laws (James Fontanella-Khan, 2012). The paper will analyse and discuss the advantages and disadvantages, privileges and drawbacks of legislation to provide board diversity. Key words: women, board of directors, company law, board diversity, governance.